Novel Thiosialosides Tethered to Metal Nanoparticles as Potent Influenza a Virus Haemagglutinin Blockers. Issue 2 (April 2013) - Feng, Fei; Sakoda, Yoshihiro; Ohyanagi, Tatsuya; Nagahori, Noriko; Shibuya, Hitomi; Okamastu, Masatoshi; Miura, Nobuaki; Kida, Hiroshi; Nishimura, Shin-Ichiro
Background: The purpose of this study was to develop a new class of influenza A virus haemagglutinin (HA) blockers by tethering thiosialoside molecules to metal nanoparticles and producing glycoclusters that enhance the affinity of HA binding by N -acetylneuraminic acid. Methods: Oxygen of the glycoside bond of sialoside was replaced with sulfur to prevent hydrolytic digestion of the N -acetylneuraminic acid residue by viral neuraminidase. Two novel thiosialosides, α-2- S -[ p -( N -levulinyl) aminophenyl]-5- N -acetylneuraminic acid (Neu5Ac- S -Lev) and α-2- S -[ m -( N -levulinyl)aminobenzyl]-5- N -acetylneuraminic acid (Neu5Ac- S -CH2 -Lev), were tethered onto the surface of metal nanoparticles via an aminooxy functionalized thiol linker in a glycoblotting reaction. Gold (Au) and silver (Ag) nanoparticles were coated simultaneously with 11-mercaptoundecyl phosphorylcholine to reduce non-specific adsorption of proteins. Phosphorylcholine self-assembled monolayercoated metals displaying clustered Neu5Ac (Neu5Ac-PCSAM-Au and Neu5Ac-PCSAM-Ag) were subjected to haemagglutination inhibition (HI) assays using the influenza A virus strain A/PR/8/1934 (H1N1). Results: Glyconanoparticles with thiosialosides had potent HI activities. In particular, Neu5Ac-PCSAM-Au with a diameter of 20 nm corresponding to 9.8 μM monosaccharide Neu5Ac was the most potent HA inhibitor. The versatility of this strategy was demonstrated by similar submicromolar HI activities of Neu5Ac-PCSAM-Ag with diameters of 50 nm and 150 nm. Conclusions: Glycosylated metal nanoparticles were designed and synthesized as potent influenza A virus HA blockers. This study may contribute to the acceleration of the discovery of a new class of nanoparticle anti-influenza drugs.